Responda a questão a seguir:
Anexos:
![](https://pt-static.z-dn.net/files/d3d/bf33b39f696b2df70fef74bc65d947b9.png)
murard305:
AJUDA
Soluções para a tarefa
Respondido por
1
Resposta:
D
Explicação passo-a-passo:
La = 2(3X^2 + 2x - 1)
Lb = -50 + 4x
La = 6x^2 + 4x - 2
La + lb = 6x^2 + 4x - 2 + (-50 + 4x)
La + Lb1 = 6x^2 + 8x - 52
entendeu ?
Perguntas interessantes
Contabilidade,
9 meses atrás
Geografia,
9 meses atrás
Matemática,
9 meses atrás
Química,
11 meses atrás
Biologia,
11 meses atrás
Português,
1 ano atrás